Preventive Activity of Muntingia calabura Fruits Extract in Aspirin-induced Gastric Ulcer Rat - Cynthia Astiti Putri; Arba P. Ramadani; Maulidha Amanati (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Gastric ulcer can be affected people at any age. One cause of this disease is NSAID usage. The aim of this study is to determine Muntingia calabura L. fruit activity for prevent ulcer using aspirin-induced gastric ulcer in rat model. Thirty male Wistar rats were divided become six groups: normal (CMC 0.5%), negative control (CMC 0.5%), positive control (omeprazole 20 mg/kg), treatment group (ethanol M. calabura L. fruit extract): I (100 mg/kg), II (200 mg/kg), and III (300 mg/kg) and given orally once a day for 9 days. On the 10th day, aspirin at a dose of 500 mg/kg was given to all groups except the normal group. Four hours after induction, all animals were sacrificed. Preventive effect against stomach ulcer were determined by calculating the index of ulcer and histopathological examination. Index ulcer of M. calabura fruit extract at all dose were different than negative group, although not significant (p<0.05). Histopathological examination of M. calabura extract at a dose of 300 mg/kg showed few inflammatory cells and congestion compared with the other treatment group. Therefore, ethanol M. calabura L. fruit extract at a dose 300mg/kg gave best activity in preventive of gastric ulcer.Keywords: aspirin, gastric ulcer, Muntingia calabura fruit